The application of means-end chain model in evaluating built environment - Mohd. Jusan, Mahmud (2004)
Means-end chain is a research model widely used in marketing researches particularly in assessing consumer goods and services. The major aim of this model is to link product’s attributes with consumer’s values. The findings using this method have been used in product’s design manipulations and marketing strategies. This model is also found to be appropriate for built-environmental researches, based on the fact that built-environments are also expressed in terms of their attributes where the relevance of the attributes is judged by the value system of the users. However, the application of this model in built-environmental studies is still experimental. The authors are currently modifying the earlier model, possibly the first application of Means-End Chain (MEC) model to be used in exploring why people change their living environment, and how this information could be used in the design process to reduce error and expenses on modification.